Clinical and laboratory awareness for an under recognized pathogen in newborn meningitis: Mycoplasma Hominis: a case report - MEMİŞOĞLU, ASLI; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA; GÜLCAN KERSİN, SİNEM; BOZAN, TURGUT (TURKISH J PEDIATRICS, 2020)
Background. Mycoplasma hominis is a well-known bacterium colonizing the genito-urinary tract. It may cause pneumonia, bacteremia, abscesses, chronic lung disease, and rarely meningitis during the newborn period. Case. A preterm infant with a birth weight of 885 grams was born at 27 weeks of gestation and had respiratory distress syndrome needing mechanical ventilation. Spontaneous intestinal perforation and grade four intraventricular hemorrhage was diagnosed on day three. Conclusion. M. hominis was accepted as the causative agent of meningitis in this case report.
Keywords: Mycoplasma hominis; newborn; meningitis; neonate; preterm; INFECTION; INFANT